Pembinaan Akhlak Siswa melalui Kegiatan Pembinaan Keagamaan di Sekolah Menengah Pertama Negeri 31 Padang - Fahira Murni Illahi; Rengga Satria (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
The purpose of this study is to find out how moral development is carried out through religious development activities at SMP Negeri 31 Padang and the supporting and inhibiting factors. Religious development activities consist of TPQ, Tahfiz, and Weekly Wirid activities. The research method uses a qualitative method with a descriptive approach. The data in the study were collected through observation, interviews and documentation. The data analysis technique was carried out using the Miles and Huberman model with the flow of data reduction, data presentation, and drawing conclusions. The results showed that moral development through TPQ activities was carried out through habituation, motivation, and advice activities. Meanwhile, moral development through Tahfiz activities is carried out through exemplary activities, invitations, and motivations. As well as moral development through weekly wirid activities, namely in the form of giving stories, reprimands and punishments, and habituation to students. The supporting factors in this religious development activity are facilities and infrastructure, good cooperation between teachers and leaders, and the wishes of students. While the inhibiting factors are the influence of friends, outside activities, and the Covid-19 situation.